Post occupancy evaluation of architectural design studio facilities - Ezz, Mohamed Salah; Mahdy, Mohamed Ahmed F.; Baharetha, Saleh; Hassanain, Mohammad A.; Gomaa, Mohammed M. (Frontiers in Built Environment, 2025)
This study presents an assessment methodology to evaluate design studio facility effectiveness by conducting a post-occupancy evaluation case study. The effectiveness of architectural studios determines how students learn in architecture schools because it affects their creativity levels and productivity and educational achievement. POE represents an essential strategy for educational facility assessment which helps verify their match with user requirements. The study follows a sequential method that initiates with a study of architectural studio importance and POE performance in academic spaces. The researchers conducted their study at Onaizah Colleges located in Qassim, Saudi Arabia by implementing both qualitative and quantitative data gathering techniques which included walkthrough inspections and semi-structured interviews and the distribution of questionnaires. The study identifies a methodical several-step system to evaluate architectural studio performance. A structured categorization of performance criteria included ten groups that evaluated functional and technical operations with behavioral capabilities across environmental comfort and spatial organization and technological implementation and user satisfaction. Educational architecture proves its dependency on fundamental features of comfort together with functionality based on the study outcomes. The framework enables professional users to methodically analyze studio layouts for enhancing their educational performance and user satisfaction. The research analysis demonstrates how user-centered design approaches must be used to improve student learning because it identifies important performance elements. The research uniquely utilizes a systematic approach to studio assessment which delivers essential information to facilities management regarding studio administration to enhance educational outcomes.